1981
DOI: 10.1080/00223980.1981.9915203
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Prenatal Stress on Rat Offsprings' Learning Ability

Abstract: The present study (N = 30 female rats, 11 male rats) was conducted to determine the effects of prenatal stress on rat offsprings' learning ability. Pregnant mothers were stressed by exposure to an SD (light) which had been paired with shock. A second group of pregnant rats was handled an equivalent amount of time, and a third group received no treatment. The offspring of the three groups were tested on several learning tasks and the handled and stressed groups were found to be inferior to the control group on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…A long line of animal research has investigated the effects of prenatal stress on the developing offspring. Consistent with the limited human data, data from animal studies have suggested that stress during pregnancy can adversely affect offspring growth (183)(184)(185)(186)(187), learning ability (188)(189)(190)(191), and attainment of developmental milestones (192). Prenatal stress may also induce persistent behavioral aberrations.…”
Section: Prenatal Stress Modelsmentioning
confidence: 81%
“…A long line of animal research has investigated the effects of prenatal stress on the developing offspring. Consistent with the limited human data, data from animal studies have suggested that stress during pregnancy can adversely affect offspring growth (183)(184)(185)(186)(187), learning ability (188)(189)(190)(191), and attainment of developmental milestones (192). Prenatal stress may also induce persistent behavioral aberrations.…”
Section: Prenatal Stress Modelsmentioning
confidence: 81%
“…This pattern suggests that MGPNS rats are more willing to sample the reinforcement; the resultant additional training experience could overcome any impairments in signaling reflected by altered EEG signals. Although the majority of studies on the F1 generation following PNS have shown impaired learning on several learning paradigms, (Smith et al, 1981;Weller et al, 1988;Hayashi et al, 1998;Lemaire et al, 2000;Szuran et al, 2000;Gue et al, 2004), some have instead reported no effect (Kapoor et al, 2009) or improved performance (Fujioka et al, 2006;Yang et al, 2006). It is conceivable that the multifaceted effects of PNS on brain function have complex effects on behavior that may improve performance on some tasks.…”
Section: Discussionmentioning
confidence: 92%
“…J. Ward (1991) Impaired sexual function Holson et al (1995), Rhees & Fleming (1981), I. L. Ward (1972), I. L. Ward & Reed (1985) Reduced propensity for social interaction Takahashi, Haglin, & Kalin (1992) Increased locomotor response to novelty Deminière et al (1992) Learning ability Impairment of maze learning Archer & Blackman (1971), Grimm & Frieder (1987) Reversal of learning set Hayashi et al (1998), Smith et al (1981) No effect Vallee et al (1997) Motor development Decreased quality of righting reflex and of climbing Barlow et al (1978), Fride & Weinstock (1984), Grimm & Frieder (1987) ated with a higher incidence of developmental deficits (e.g., Dewey, Crawford, Creighton, & Sauve, 1999;Pharoah, Stevenson, Cooke, & Stevenson, 1994). Another explanation for the discrepancy in findings between Worlein and Sackett's (1995) and the Schneider (1992b) studies may be the tool they used to assess motor development in the offspring.…”
Section: Prenatal Stress and Behavior Of Nonhuman Primate Offspringmentioning
confidence: 99%